Pengembangan Buku Ajar Berbasis Scientific Approach Pada Mata Pelajaran Akuntansi Keuangan Kelas XI Semester Genap SMK Negeri 1 Sooko Mojokerto - Nana Febriana; Agung Listiadi (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2020)
The purpose of this study to produce and analyze the results of advisability and student responses to the textbook based on scientific approach on financial accountiingg subjects. This textbook was tested by material experts, linguists, and graphic, tested on 20 XI grade Financial Accounting students at Sooko Mojokerto State Vocational School. The research method used 4D development model by Thiagarajan without being spread. This study gets results from the validation of material experts by 91.70%, validation of linguists 80%, graphic validation by 86.67% and students responses by 96%. The recapitulation was successfully obtained 88.59% and it can be concluded that the textbooks developed were very feasible to use.